2021
DOI: 10.1155/2021/7678931
|View full text |Cite
|
Sign up to set email alerts
|

Housing Price Prediction Based on Multiple Linear Regression

Abstract: In this paper, the author first analyzes the major factors affecting housing prices with Spearman correlation coefficient, selects significant factors influencing general housing prices, and conducts a combined analysis algorithm. Then, the author establishes a multiple linear regression model for housing price prediction and applies the data set of real estate prices in Boston to test the method. Through the data analysis and test in this paper, it can be summarized that the multiple linear regression model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Since the sample companies from 2012 to 2015 are not the same, and the short time is only four years, the four-year sample is aggregated as cross-sectional data for regression analysis. Table 5 shows the multiple regression [24][25][26][27][28][29] results of the impact of carbon information disclosure on corporate value. It can be seen from Table 5 that the overall fitting degree is 0.336, indicating that the selection of explanatory variables in the model is reasonable.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%
“…Since the sample companies from 2012 to 2015 are not the same, and the short time is only four years, the four-year sample is aggregated as cross-sectional data for regression analysis. Table 5 shows the multiple regression [24][25][26][27][28][29] results of the impact of carbon information disclosure on corporate value. It can be seen from Table 5 that the overall fitting degree is 0.336, indicating that the selection of explanatory variables in the model is reasonable.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%
“…The study showed that the price has a strong linear correlation with GDP, the total population in a certain area and some other factors. So, the conclusion was that it is reliable to predict the house price by linear regression model [5]. Dang and Yang studied the house prices in Tangshan and divided the factors into demand factors and supply factors.…”
Section: Related Reasearchmentioning
confidence: 99%
“…People prefer houses that are close to these places for convenience and shorter commuting times. Overall, these factors, including house features, environmental conditions, and transportation accessibility, play a significant role in determining the prices of real estate properties (Zhang, 2021). Ghosalkar et al (2018) researched the importance of studying the cost of land due to its constantly changing prices.…”
Section: Literature Reviewmentioning
confidence: 99%